THE POSSIBILITY TO USE POLARIMETRIC RADAR FOR ATMOSPHERIC TURBULENCE INTENSITY ESTIMATE - Averyanova, Yuliya (Proceedings of National Aviation University (archive), 2012)
Approach, that is presented in this paper proposes to estimate the turbulence intensity by spectral components of polarization signals as random process. It allows to decrease time for signal processing. We consider turbulence as stochastic process. Liquid hydrometeors that are the cause of polarization spectrum appearance are considered as the filter from which the output signal is taken for further transmitting and processing. The requirements to the line for polarization spectrum transmission are represented. The calculations show that the transmission line should be capable to transmit frequencies from about zero to those that are determined by the sampling frequency that is enough to define polarization spectrum parameters as a random process with given accuracy.